Waste fish oil as an alternative renewable fuel for IC engines - Hissa, M.; Niemi, S.; Ovaska, T.; Niemi, A. (Estonian University of Life Sciences, 2021)
Bio-oils are potential fuels for internal combustion engines because of they have advantageous properties such as biodegradability, renewability, high oxygen content and low sulphur. However, the high viscosity, surface tension, and density of crude bio-oils pose challenges for engine use. Those properties affect fuel spray characteristics, mixture formation and combustion. In turn, these impact engine, efficiency, power and emissions. This study investigated the use of crude fish oil (FO) at medium and low engine-loads at two engine speeds in an off-road engine. The injectors had 6-hole high flow rate tips. The results were compared with those of fossil diesel fuel oil (DFO). Fish oil increased hydrocarbon (HC), carbon monoxide (CO) and partly oxides of nitrogen (NOx) emissions. Smoke number, however, decreased. Crude fish oil also showed lowered total particle number (TPN) at low load at low engine-speed compared with DFO.
Keywords: diesel engine; bio-oil; combustion; gaseous emissions; particle number; diesel engines; fi=Energiatekniikka|en=Energy Technology|